Strengthened convexity of positive operator monotone decreasing functions - Kirihata, Megumi; Yamashita, Makoto (MATHEMATICA SCANDINAVICA, 2020)
We prove a strengthened form of convexity for operator monotone decreasing positive functions defined on the positive real numbers. This extends Ando and Hiai’s work to allow arbitrary positive maps instead of states (or the identity map), and functional calculus by operator monotone functions defined on the positive real numbers instead of the logarithmic function.